7 - Hidden Processes of Reconciliation in Mozambique: The Entangled Histories of Truth-seeking Commissions held between 1975 and 1982 - Meneses, Maria Paula (Africa Development, 2021)
The southern Africa region has witnessed, over the last 50 years, several episodes of violent conflicts, and Mozambique is no exception. The dominant perspective of the Global North on transition to democracy insists on reinforcing a eurocentric version of modernity, symbolized by a linear transition towards a single legal system and nationhood. This dominant international model of justice reproduces violence in the form of epistemicide and privatization of violence. If courts cannot end civil wars, what are the alternatives? This article, which is focused upon Mozambique and based upon interviews and archival data, aims to explore the extent to which the multiple, almost invisible and silenced processes of national reconciliation can find expression within methodologies of national reconciliation processes. Specific emphasis is placed upon the analysis of initiatives (in the 1970s and 1980s) to deal with ‘traitors of the revolution’ in open organized meetings that produced little-known practices of national reconciliation. It is in such a context where the limits of the discourse about ‘universal jurisdiction’ and criminalization of perpetrators of violence are arguably best understood, and where alternatives can find their strongest manifestations and most radical expressions. Maria Paula Meneses, Centre for Social Studies, Colégio de Sao Jerónimo, Coimbra University, Portugal. Email: mpmeneses@gmail.com